Offensive effectiveness in the female elite handball in numerical superiority situations - Amatria, M.; Lapresa, D.; Martin Santos, C.; Perez-Turpin, J. A (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2020)
Handball, despite being one of the most practiced sports in Europe, does not arouse great interest forthe scientific community in its female modality. Taken into account the relevance of situations of numerical superiority in the matches, this research aims to analyse the offensive, effective and ineffective sequences that occur in elite women's handball in situations of numerical offensive superiority, during the World Championship held in Sweden in 2016. For this purpose, the observational methodology and the sequential analysis of delays have been used. The results obtained reveal a successful offensive game pattern, that is, that the offensive sequence concludes in goal, a game pattern that uses an unstructured tactical system, regardless of itsonset form. It uses the first wave counterattack as the main offensive technique, to finish the actions with situations of 1vs0.